1970
DOI: 10.3126/jncs.v25i0.3305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alloying Elements on the Corrosion Behavior of Sputter–deposited Zr–(12–21)Cr–W Alloys in 0.5 M NaCl Solution

Abstract: The synergistic effect of the simultaneous additions of tungsten and zirconium in the sputter-deposited amorphous or nanocrystalline

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…It has been reported that the sputterdeposited amorphous or/and nanocrystalline tungsten-based W-xTi (Bhattarai 2009a, 2009b, Bhattarai et al 1995, Sharmah et al 2007), W-xNi (Bhattarai 2001, Sah & Bhattarai 2008), W-xNb (Bhattarai 2011a, Bhattarai et al 1998a, 1998b, Jha & Bhattarai 2008), W-xCr (Bhattarai et al 1998c, Basnet and Bhattarai 2010, WxTa (Bhattarai 2011b, 2012a, Bhattarai & Baral 2013, Bhattarai et al 1998d), W-xMo (Bhattarai 2006, 2012b, Khadka & Bhattarai 2010, W-xZr (Bhattarai et al 1997, Shrestha & Bhattarai 2010, W−xZr−yCr (Aryal & Bhattarai 2010, Bhattarai 2010a, 2011c, 2011d, Kumal & Bhattarai 2011) and W−xCr−yNi (Bhattarai 2009c, 2010b, Bhattarai & Kharel 2009-10, Kharel & Bhattarai 2009) alloys were spontaneously passivated showing significantly higher corrosion resistance than those of alloy-constituting elements in aggressive solutions. The significant improvement of the corrosion resistance properties of these alloys is attributed to the formation of double oxyhydroxide passive films containing both tungsten and alloyconstituting metal cations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the sputterdeposited amorphous or/and nanocrystalline tungsten-based W-xTi (Bhattarai 2009a, 2009b, Bhattarai et al 1995, Sharmah et al 2007), W-xNi (Bhattarai 2001, Sah & Bhattarai 2008), W-xNb (Bhattarai 2011a, Bhattarai et al 1998a, 1998b, Jha & Bhattarai 2008), W-xCr (Bhattarai et al 1998c, Basnet and Bhattarai 2010, WxTa (Bhattarai 2011b, 2012a, Bhattarai & Baral 2013, Bhattarai et al 1998d), W-xMo (Bhattarai 2006, 2012b, Khadka & Bhattarai 2010, W-xZr (Bhattarai et al 1997, Shrestha & Bhattarai 2010, W−xZr−yCr (Aryal & Bhattarai 2010, Bhattarai 2010a, 2011c, 2011d, Kumal & Bhattarai 2011) and W−xCr−yNi (Bhattarai 2009c, 2010b, Bhattarai & Kharel 2009-10, Kharel & Bhattarai 2009) alloys were spontaneously passivated showing significantly higher corrosion resistance than those of alloy-constituting elements in aggressive solutions. The significant improvement of the corrosion resistance properties of these alloys is attributed to the formation of double oxyhydroxide passive films containing both tungsten and alloyconstituting metal cations.…”
Section: Introductionmentioning
confidence: 99%
“…Since the extremely high corrosion resistance amorphous iron-base alloys were reported in 1970's (Hashimoto & Masumoto 1976, Hashimoto et al 1976, 1979, Naka et al 1974, 1976, varieties of corrosion-resistant rapidly quenched and sputter-deposited alloys were developed during the last four decades. Since 1990's, it has been reported that the sputter-deposited binary tungsten-titanium (Bhattarai 1998a, b, Bhattarai et al 1995, tungsten-zirconium (Bhattarai 1998, Bhattarai et al 1997, Shrestha & Bhattarai 2010, tungsten-chromium (Basnet & Bhattarai 2010, Bhattarai 1998, Bhattarai et al 1998, tungsten-niobium (Bhattarai 1998Bhattarai et al 1998b, Jha & Bhattarai 2008, tungstentantalum (Bhattarai 1998b, 2012, tungsten-molybdenum (Bhattarai 1995, 2006b, Khadka & Bhattarai 2010 and tungsten-nickel (Bhattarai 1995, Bhattarai et al 2007, Sah & Bhattarai 2008, and ternary tungsten-based (Aryal & Bhattarai 2010a, b, 2011c, d, Kumal & Bhattarai 2010 alloys showed higher corrosion resistance than those of alloy-constituting elements in different corrosive environments.…”
Section: Introductionmentioning
confidence: 99%
“…The average corrosion rate of the alloys was estimated from the weight loss after immersion for 240 h in 1 M NaOH solution open to air at 25 o C. The weight loss for each alloy specimen was estimated two times or more and the average corrosion rate was calculated as described elsewhere 4,30 . The time dependence of the corrosion rate of the W-Zr-(15-33)Cr alloys was also estimated at various time intervals.…”
Section: Experimental Methodsmentioning
confidence: 99%